FAKTOR YANG BERPENGARUH TERHADAP DURABILITAS, STRUKTUR DAN MATERIAL RUMAH SEDERHANA - -, Marwati (Teknosains, 2011)
This study aims    to  investigate   the factors affect the material and structure of the  house, and also the age of the building has a strong influence on the durability. Degradasi of Structure and house material not yet reached the simple house endurance standard    (20 year). So this research aim to identify the factor influencing durabilitas of structure and simple house material. This research take  house type 36 in Perumnas Bumi Tamalanrea, Chief Of Village Tamalanrea, Subdistrict Tamalanrea, Town Makassar. Population as much 2342 house and sampel selected in group as much 117 house from 18 block . Data analysed statistically in the form of tabulation traverse. Interpretation opened by joining analysis qualitative and kuntitatif of] scale ordinal. Result of Research show the Factor age of building have an effect on the strength to durabilitas. Keyword: structure, material, degradation